Assessment of quality of life in patients with visual impairments using a new visual function questionnaire: the VFQ-J11 - Nakano T (Dove Medical Press, 2016)
Tadashi Nakano,1 Motoko Kawashima,2 Yoshimune Hiratsuka,3 Hiroshi Tamura,4,5 Koichi Ono,6 Akira Murakami,3 Kazuo Tsubota,2 Masakazu Yamada7,8 1Department of Ophthalmology, Jikei University School of Medicine, 2Department of Ophthalmology, Keio University School of Medicine, 3Department of Ophthalmology, Juntendo University Graduate School of Medicine, Tokyo, 4Department of Ophthalmology & Visual Sciences, Kyoto University, 5Division of Medical Information Technology & Administration Planning, Kyoto University Hospital, Kyoto, 6Department of Ophthalmology, Juntendo Tokyo Koto Geriatric Medical Center, 7National Institute of Sensory Organs, National Hospital Organization Tokyo Medical Center, 8Department of Ophthalmology, Kyorin University, Tokyo, Japan Background: The purpose of the present study was to assess the vision-related quality of life (QOL) of visually impaired patients using the Japanese 11-item National Eye Institute Visual Function Questionnaire (VFQ-J11). Comparisons with the 25-item version (VFQ-25) and the EuroQoL Index using a large group of patients with various degrees of impairments and various causative diseases were performed.Methods: A total of 232 visually impaired Japanese patients were recruited from six ophthalmology departments in Japan. Information on ophthalmic findings and patient backgrounds was collected, and information on QOL and utility assessments was collected from the patients by means of survey questionnaires.Results: The average age of patients was 69.6±14.3 years. Both the vision-related QOL scores (VFQ-25 composite and VFQ-J11) were significantly associated with better and worse visual acuity (VA) in visually impaired subjects (all P<0.01). VFQ-J11 was comparable to VFQ-25 regardless of causative diseases. VFQ-25 composite and the VFQ-J11 scores were concurrently associated with a range of systemic medical disorders. EuroQoL Index had a significant association with better eye VA (P<0.01), but not with worse eye VA, or any systemic disorders.Conclusion: VFQ-J11 provides valid data on vision-related QOL and is less of a burden for patients with vision problems. Keywords: quality of life, utility, visual acuity, visual impairment, VFQ-25, EQ-5D